Effects of Annealing Temperature and Time on Properties of Thermoplastic Polyurethane Based on Different Soft Segments/Multi-Walled Carbon Nanotube Nanocomposites - Kittimon Jirakittidul; Darawan Limthin; Sarita Mahithithummathorn; Seenam Phaewchimphlee (My University, 2023)
Typically, polymer chains can move under the annealing process, resulting in an ordered structure arrangement. This causes an improvement in nanocomposite properties and in the dispersion of filler. In this research, annealed thermoplastic polyurethane (PU)/multi-walled carbon nanotube (MWCNT) nanocomposites were studied to investigate the effect of annealing on the selective dispersion of MWCNTs. PU matrices were composed of two different soft segments, i.e., polyether (PU-Ether) and polyester (PU-Ester). Nanocomposites were prepared by the melt mixing process and annealed at 80 to 120 °C for 6 to 24 h. The increases in annealing time and temperature resulted in microphase separation in segmented PU and the orientation of crystalline structures in the segregated hard domain. Nanocomposites showed higher electrical conductivity after annealing. This implies that the movement of PU chains during heat treatment encouraged the development of the MWCNT network. However, the increase in ordered structures could obstruct the MWCNT network, resulting in lower electrical conductivity levels. Considering the selective dispersion of MWCNT in PU matrices, it was found that MWCNTs dispersed in soft segments of PU-Ether, leading to a significant decrease in elongation at the break after annealing. On the other hand, a decrease in elasticity of PU-Ester nanocomposites was not observed as a result of MWCNT dispersal in hard segments.
Keywords: Thermoplastic polyurethane; Carbon Nanotubes in Composites